Thematic Learning Based On Physical Literacy for Early Children - Asep Suherman; Adang Suherman; Tite Juliantine; Agus Mahendra (JUARA : Jurnal Olahraga, 2021)
This study aims to develop a thematic learning model based on physical literacy for early childhood. This needs to be done because physical literacy can increase children's physical activity through various kinds of contextual movements so that learning becomes more fun, optimizes children's motor development, which will impact the development of other aspects, and reduce the risk of obesity. The research method used is a literature study with an integrative review approach with literature sources in books, international modules, and national and international research journals. Based on the literature review results, the initial design of the thematic learning model based on physical literacy consists of the phases of apperception, warming up, observation, playing, reflection, and cooling down. In each of these learning phases, physical literacy domains are integrated, including social, psychological, physical, and cognitive. Integrating all parts of physical literacy in each stage of learning is carried out so that the stimulus for early childhood development can run comprehensively.